2017
DOI: 10.1088/1748-0221/12/05/c05010
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the ionization yield of nuclear recoils in liquid argon using a two-phase detector with electroluminescence gap

Abstract: A: A measurement of ionization yields in noble-gas liquids is relevant to the energy calibration of nuclear recoil detectors for dark matter search and coherent neutrino-nucleus scattering experiments. In this work we further study the ionization yield of nuclear recoils in liquid Ar, using a two-phase detector with an electroluminescence gap and DD neutron generator. The ionization yields of nuclear recoils in liquid Ar were measured at 233 keV and electric fields of 0.56 and 0.62 kV/cm; their values amounted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The generalized version of the two-phase detector with EL gap used in our current studies [3,4,6,9] is shown in Fig. 1.…”
Section: Structure Of the Thgem-based Two-phase Detectormentioning
confidence: 99%
See 2 more Smart Citations
“…The generalized version of the two-phase detector with EL gap used in our current studies [3,4,6,9] is shown in Fig. 1.…”
Section: Structure Of the Thgem-based Two-phase Detectormentioning
confidence: 99%
“…To the best of our knowledge, no one has simulated THGEM performance in liquid argon thus far; it has been done for the first time in the present work. Figure 1: Generalized version of the two-phase detector with EL gap used in [3,4,6,9] (not to scale). The 4 MΩ resistance defining the voltage across THGEM0 is referred to as R T HGEM0 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noble liquid (NL) radiation detectors are a widely used tool in modern particle physics experiment. These detectors enable a variety of research programs ranging from neutrino physics [1,2] and dark matter searches [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] to other rare-event measurements [21][22][23][24][25][26][27][28][29][30][31]. In recent years, significant effort has been committed to exploring how large-scale NL detectors can answer pressing questions in these fields.…”
Section: Introductionmentioning
confidence: 99%
“…The main purpose of this work is to provide reference data on the emission spectrum of a 109 Cd gamma-ray source. Such a radioactive source is used to calibrate the energy scale of a two-phase argon detector, which is being developed in our laboratory for dark matter search and low-energy neutrino experiments [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%